"It Would Be Nice If": Analysis of Transition Experiences Through Grand Challenges. (September 2021) - Kucharczyk, Suzanne; Thomas, Johanna; Schaefer Whitby, Peggy
The adult outcomes of youth with disabilities continue to lag behind those of their peers without disabilities, especially for youth living in rural communities. Interdisciplinary teaming is identified as an important component of effective transition planning. Transition planning and collaborative teaming are challenged further in rural communities due to lack of resources, distances between services and providers, and access for youth and their families. Social workers, given their multisystem perspective on aligning youth and family needs with resources, may be well poised, though currently underutilized, to address the challenges of transition in rural contexts. Through the transition experiences of 20 families and young adults with high need disabilities from a rural southern state, this study analyzes the potential alignment between the tenets of the Individuals with Disabilities Education Act for transition and the priorities of social work described in the Grand Challenges. Implications for practice and policy for special education transition planning in rural communities are offered.